2001
DOI: 10.1074/jbc.m007236200
|View full text |Cite
|
Sign up to set email alerts
|

Plant Initiation Factor 3 Subunit Composition Resembles Mammalian Initiation Factor 3 and Has a Novel Subunit

Abstract: Eukaryotic initiation factor 3 (eIF3) is a multisubunit complex that is required for binding of mRNA to 40 S ribosomal subunits, stabilization of ternary complex binding to 40 S subunits, and dissociation of 40 and 60 S subunits. These functions and the complex nature of eIF3 suggest multiple interactions with many components of the translational machinery. Recently, the subunits of mammalian and Saccharomyces cerevisiae eIF3 were identified, and substantial differences in the subunit composition of mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 73 publications
3
87
0
Order By: Relevance
“…A strong support to the notion of HSPC021 being tightly associated with eIF3 comes also from results published during completion of this work on the A. thaliana eIF3. Indeed, it has been reported that eIF3 purified from this organism includes 12 subunits, one of them corresponding to the A. thaliana homolog of HSPC021 (38). In agreement with the data published by Burks et al, the results presented in this paper show that HSPC021 strongly binds the eIF3 translation initiation factor in mammals.…”
Section: Resultssupporting
confidence: 82%
“…A strong support to the notion of HSPC021 being tightly associated with eIF3 comes also from results published during completion of this work on the A. thaliana eIF3. Indeed, it has been reported that eIF3 purified from this organism includes 12 subunits, one of them corresponding to the A. thaliana homolog of HSPC021 (38). In agreement with the data published by Burks et al, the results presented in this paper show that HSPC021 strongly binds the eIF3 translation initiation factor in mammals.…”
Section: Resultssupporting
confidence: 82%
“…Thus, it is possible that the activities of eIF3 from higher eukaryotes are modulated by association of the five core subunits with Int-6 and the other eIF3 subunits not found in S. cerevisiae. Interestingly, the recent progress in sequencing the entire genome of fission yeast Schizosaccharomyces pombe has revealed that it encodes the four orthologs of noncore eIF3 subunits, in addition to orthologs of the five core subunits (14). Thus, S. pombe eIF3 may resemble mammalian eIF3 in containing several polypeptides in addition to the five core subunits present in budding yeast.…”
Section: Mouse Mammary Tumor Virus (Mmtv)mentioning
confidence: 99%
“…To identify the biological role of Int-6 and decipher the consequences of its truncation, it was important to establish the role of Int-6 in translation initiation as a part of eIF3. Thus far, eIF3 has been purified from mammalian cells (10,11), wheat germ (12,13), A. thaliana (14), and budding yeast Saccharomyces cerevisiae (15)(16)(17). Mammalian eIF3 associates with the 40 S ribosome and stimulates the binding of both mRNA and Met-tRNA i Met (10,11).…”
Section: Mouse Mammary Tumor Virus (Mmtv)mentioning
confidence: 99%
“…With 12 subunits in plants, eIF3 is by far the largest of these factors (Burks et al, 2001). eIF3 stimulates binding of the ternary complex (eIF2, Met-tRNA Met , GTP) to the 40S ribosome, inhibits premature association of 40S and 60S subunits, and may serve as a bridge between eIF4G and the 40S ribosome during the early stage of initiation (Hinnebusch, 2006;Siridechadilok et al, 2005).…”
Section: Introductionmentioning
confidence: 99%